N 2d hydrodynamic modelling of a tidal inlet using telemac. case study of “de ijzermonding - Nolivos Alvarez, Indira (2009)
Restoring lost and degraded wetlands is essential to ensure the health of our watersheds. Over the past 200 years, historic tidal wetlands have been destroyed at an alarming rate (EPA factsheet, 2001). Such reduction of tidal wetlands hamper various functions like water quality protection, habitat for fish and other wildlife, and flood protection. Unless reserving the tide of wetland loss, the quality of waters will continue to be threatened and part of natural haritage will be lost. Restoration is the return of a degraded wetland or former wetland to its preexisting, naturally functioning condition, or a condition as close to that as possible (EPA factsheet, 2001). It is a complex process that requires expertise, resource and commitments from many different stakeholders. The timing of the restoration activities will be important not only to avoid disturbing wildlife species but also to ensure that earlier phases of the restoration have been successful before altering other habitat. It will be necessary to carefully monitor conditions as the restoration proceeds, and adapt the restoration plans to ensure overall project goals are achieved. Restoration projects require planning, implementation, monitoring and management, using a team with expertise in ecology, hydrology, engineering and environmental planning. Shallow estuaries are extremely dynamic regions where fluid motions are associated with both surface waves and current. Its restoration requires a number of factors to be taken into consideration. The proper design as well as construction and maintenance of restoration work needs the exact knowledge of hydrodynamics. There are several physical conditions that will affect the feasibility of restoring tidal marshes: presence of channels, availability of material for levees, pond subsidence, potential for flooding, and infrastructure impediments (bridges, harbours,lock gates, etc.). The insight of spatial and temporal variability of flow velocity is the major factor controlling the morphology of the system. The erosion and sedimentation processes of tidal marsh have an important effect on the proper functioning of estuary. The use of numerical models in the restoration of a nature reserve has a great importance in terms of development and evaluation of ever changing tidal system. Therefore, the hydrodynamic investigation is chosen to be a major part of a nature reserve restoration project.